My youngest, there's no one like you - Leman, Kevin; Leman, Kevin, II (Grand Rapids, Mich. : Revell, 2005)
When Youngest Cub complains that it is hard to be the youngest, Mama Bear looks at family photos with him and explains how much he means to her.
"A birth order book"--P. [4] of cover.
Keywords: Youngest child -- Fiction; Mother and child -- Fiction; Photographs -- Fiction; Bears -- Fiction